Effect of Fartlek Exercises by Ascending and Descending Styles to Development the Coordination, Balance, and Lay-Up Shot for Young of Basketball - Qahtan Adnan Shamran; Aied Hussain Abdul Ameer; Maytham Lateef Ibraheem Barben (Institute of Medico-legal Publications Pvt Ltd, 2021)
The research objectives were defined in preparing fartlek exercises in both ascending and descending styles,to develop coordination, balance, and Lay-up shot for young basketball players, and also to identify theeffect of the ascending and descending Fartlek exercises on the development of coordination, balance, andLay-up shot for youth basketball players . The researchers used the experimental approach to design the twoequal groups with the pre and post-tests, and on the main research sample of (12) players from the Al HillaSports Basketball Club, the youth group, aged (16-17) years, the sample was divided into two groups with(6) players for each group, and the first experimental group followed the Fartlek exercises in an ascendingmanner, while the second experimental group followed the fartlek exercises in a descending manner, and aparity process was performed in the pre-tests, and then implementing the vocabulary of the fartlek exercisesin the ascending and descending methods on the first and second experimental research group within aperiod that lasted (6) weeks and at (3) training units per week, thus the total number of units reached (18)units and the time of the educational unit was (90) minutes